India’s New Role in East Asia: Implications for Mongolia - Soni, Sharad K (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i13.6 Mongolian Journal of International Affairs No.13 2006 pp.32-41